The Effect of Conspicuous Consumption on Social Identity Formation in the Branded Clothing Sector: The Mediating Effect of Product Symbolism - Nirupama, M.I.; Galdolage ., B.S. (Faculty of Management Studies and Commerce University of Sri Jayewardenepura, 2024)
Conspicuous consumption is regarded as a status-related consumption. Thus, products represent social standing, identity, and affiliation with a group. People use the symbolic meaning of products as an external manifestation of consumer identity and social connection to society. Hence, this study focuses on young adults’ social identity formation aged 20-35 through the consumption of products that carry identity-related attributes with special reference to the branded clothing sector. The main objective of this study was to examine the effect of conspicuous consumption on social identity formation and to test the mediating effect of product symbolism on the relationship between conspicuous consumption and social identity formation in the branded clothing sector of young adults. Using the Snowball sampling technique, data was gathered via a survey from 185 young adults aged 20-35 in Sri Lanka who wear branded clothes. The collected data were analyzed using regression analysis with the assistance of SPSS software. The findings revealed that the effect of conspicuous consumption on social identity formation mediated through product symbolism is statistically significant. Knowing that young adults are driven by conspicuous consumption, marketers can differentiate their strategies. In markets where status and self-identity are highly regarded, marketers should ensure that their products offer consumers a unique value proposition to make a positive and distinct self-image. Since there hasn't been much research on the mediating role of product symbolism in the relationship between conspicuous consumption and the formation of social identities in both Sri Lankan and other national contexts, this study fills a gap in the body of existing literature.
Keywords: Conspicuous Consumption, Social Identity Formation, Product Symbolism, Branded Clothing, Young Adults